2013
DOI: 10.1128/aem.01393-13
|View full text |Cite
|
Sign up to set email alerts
|

Gains of Bacterial Flagellar Motility in a Fungal World

Abstract: The maintenance of energetically costly flagella by bacteria in non-water-saturated media, such as soil, still presents an evolutionary conundrum. Potential explanations have focused on rare flooding events allowing dispersal. Such scenarios, however, overlook bacterial dispersal along mycelia as a possible transport mechanism in soils. The hypothesis tested in this study is that dispersal along fungal hyphae may lead to an increase in the fitness of flagellated bacteria and thus offer an alternative explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
69
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 37 publications
8
69
1
Order By: Relevance
“…Karsten. Under the conditions used, the mycelium of Lyophyllum showed hydrophobicity, thus inhibiting the formation of a water film around the hyphae, which might be necessary for bacterial attachment and dispersal (Pion et al, 2013). However, Warmink et al (2011) showed that B. terrae BS001 could migrate together with Lyophyllum sp.…”
Section: Resultsmentioning
confidence: 98%
“…Karsten. Under the conditions used, the mycelium of Lyophyllum showed hydrophobicity, thus inhibiting the formation of a water film around the hyphae, which might be necessary for bacterial attachment and dispersal (Pion et al, 2013). However, Warmink et al (2011) showed that B. terrae BS001 could migrate together with Lyophyllum sp.…”
Section: Resultsmentioning
confidence: 98%
“…The sliding hypothesis can be tested with mutant strains defective in surfactant production (21). Interestingly, Pseudomonas putida bacteria lacking flagella lose their ability to migrate along hyphae, suggesting that unlike S. marcescens, they rely entirely on flagella to move along the fungal mycelium (22).…”
Section: Discussionmentioning
confidence: 99%
“…The dispersal of microorganisms is recognized as a key factor for soil ecological functions (1,(46)(47)(48), such as the promotion of microbial diversity or the turnover of chemicals. Bacterial dispersal along fungal mycelia has been shown for numerous bacterial species and fungi (18,49,50) and hence may be of special relevance in unsaturated soil systems. Fungi constitute up to 75% of the soil microbial biomass, with a length of 10 2 to 10 4 m hyphae per g of soil (12,51).…”
Section: Effects Of Dispersal Network On Bacterial Dispersal At Diffmentioning
confidence: 99%
“…Glass fibers were used to simulate hyphae surrounded by liquid films (16,18) and to exclude effects of hyphal activities on bacterial growth and nutrition (38)(39)(40)(41) to avoid additional complexity that might mask effects attributable to the promotion of bacterial dispersal at a lowered ⌿ m .…”
Section: Effects Of Dispersal Network On Bacterial Dispersal At Diffmentioning
confidence: 99%
See 1 more Smart Citation